Comparisons of leg, arm, and back muscle oxygenation during rowing exercise using near infrared spectroscopy - Saacks, L. (Appalachian State University, 2020)
Introduction:Indoor rowing is an increasingly popular mode of exercise that provides a total-body workout. In a proper rowing motion, muscles in the leg, back, and arm are utilized sequentially(Secher, 1993). These different muscle groups, which vary in terms of muscle fiber composition, all consume oxygen during rowing exercise. However, it is unknown how changes in muscle oxygenation during an acute bout of rowing may differ between these primary working muscles.Purpose: The purpose of this study was to assess the deoxygenation in exercising muscles based on their oxidative properties and to further the research into new near infrared spectroscopy (NIRS) technology.Methods:Male and female college-age subjects were recruited for this study.NIRS devices wereplaced on the vastus lateralis, biceps brachii, and erector spinae muscles to measure oxygen saturation during rowing exercise. Subjects rowedfor two minutes each at three different relative (i.e., based on percent of maximal power output) exercise intensities, in a randomized order. Muscle oxygen saturation(SmO2) and total hemoglobin content (THb)werecontinuously monitored during each stage, as well as in the rest periods between each stage.Results:Data indicate strikingly similar trends in muscle oxygen consumption in men and women during rowing. Additionally, SmO2in the vastus lateralis decreasedto the greatest degree out of the three muscle groups, regardless of intensity. The deoxygenation of the biceps and erector muscles, however, were not significantly different from each other.THb, like SmO2, increased from rest to exercise, but was not significantly different between the exercise intensities. The difference between male and female THb across all time periods was significant, as males exhibited a higher THb than females. Discussion:Many results of the study 4proved to be insignificant, mostlikely due to a multitude of variables, including the small sample size, the untrained status of the subjects, and the low reliability of current NIRS devices at high intensity exercise. More research should be performed to further understand the oxidative properties of various muscles groups during rowing exercise as well as advance the reliability of NIRS technology in an athletic setting.